Vitamin C Administration by Intravenous Infusion Increases Tumor Ascorbate Content in Patients With Colon Cancer: A Clinical Intervention Study - Dachs, Gabi U.; Gandhi, Jamish; Wohlrab, Christina; Carr, Anitra C.; Morrin, Helen R.; Pullar, Juliet M.; Bayer, Simone B.; Eglinton, Tim W.; Robinson, Bridget A.; Vissers, Margreet C. M. (Frontiers in Oncology, 2021)
The use of high dose ascorbate infusions in cancer patients is widespread, but without evidence of efficacy. Several mechanisms whereby ascorbate could affect tumor progression have been proposed, including: (1) localised generation of cytotoxic quantities of H2O2; (2) ascorbate-dependent activation of the 2-oxoglutarate-dependent dioxygenases that control hypoxia-inducible factors (HIFs) and that are responsible for the demethylation of DNA and histones; (3) increased oxidative stress induced by dehydroascorbic acid. We hypothesise that the dysfunctional vasculature of solid tumors results in compromised delivery of ascorbate to poorly perfused regions of the tumor and that this ascorbate deficit acts as an additional driver of the hypoxic response via upregulation of HIFs. Using a randomised ‘therapeutic window of opportunity’ clinical study we aimed to determine whether ascorbate infusions affected tumor ascorbate content and tumor biology. Patients with colon cancer were randomised to receive infusions of up to 1 g/kg ascorbate for four days before surgical resection (n = 9) or to not receive infusions (n = 6). Ascorbate was measured in plasma, erythrocytes, tumor and histologically normal mucosa at diagnostic colonoscopy and at surgery. Protein markers of tumor hypoxia or DNA damage were monitored in resected tissue. Plasma ascorbate reached millimolar levels following infusion and returned to micromolar levels over 24 h. Pre-infusion plasma ascorbate increased from 38 ± 10 µM to 241 ± 33 µM (p < 0.0001) over four days and erythrocyte ascorbate from 18 ± 20 µM to 2509 ± 1016 µM (p < 0.005). Tumor ascorbate increased from 15 ± 6 to 28 ± 6 mg/100 g tissue (p < 0.0001) and normal tissue from 14 ± 6 to 21 ± 4 mg/100 g (p < 0.001). A gradient of lower ascorbate was evident towards the tumor centre in both control and infusion samples. Lower expression of hypoxia-associated proteins was seen in post-infusion tumors compared with controls. There were no significant adverse events and quality of life was unaffected by ascorbate infusion. This is the first clinical study to demonstrate that tumor ascorbate levels increase following infusion, even in regions of poor diffusion, and that this could modify tumor biology.